Effectiveness of professional training of Sub Assistant Agriculture Officers (Journal of the Bangladesh Agricultural University, 2020)
The study attempted to determine the effectiveness of professional training of Sub Assistant Agriculture Officers (SAAOs) in four upazilas under Mymensingh district namely, Mymensingh sadar, Bhaluka, Trishal and Muktagachha. Data were collected from a sample of 80 skilled, experienced and trained SAAOs who were selected randomly among 139 SAAOs during 01 October to 07 November, 2018 by using a structured interview schedule. More than half of the SAAOs (51.25%) perceived professional training as highly effective, while 46.25% and 2.5% of them perceived training as medium and low effective, respectively. Among 27 training related activities, ‘training programs increased proficiency in work’ got an average maximum score of 2.44 and ‘transport facilities were provided’ got an average lowest score of 1.49. Among eleven selected characteristics: level of education, training received, social mobility, communication exposure, attitude of SAAOs towards DAE management and job satisfaction were significantly related to the effectiveness of professional training. The study revealed that there is an ample scope to increase the effectiveness of professional training of the SAAOs. It is therefore recommended that the Department of Agricultural Extension (DAE) and other training providing organizations can offer more funds and attention to organize more related training to make the SAAOs more capable, self-confident and productive extension workers.J Bangladesh Agril Univ 18(1): 189–193, 2020https://doi.org/10.5455/JBAU.94763